Design and Construction of Greenhouses for Protected Cultivation of Crops - Bhatnagar, P. R. (Indian Farming, 2015)
Greenhouse refers to a structure which provide relatively better environment for plant growth. The goal is to create congenial temperature and relative humidity in desired range for best growth and reproduction. In the present day commercial greenhouse, also called as polyhouse, a relatively rigid frame (made of GI pipes, angle iron, bamboo or wooden) is covered with polythene sheet (UV stabilized 200 micron LDPE sheet) as covering which entraps the solar energy to increase the temperature and provide light for plant propagation. The strength of the rigid, which is made a bit flexible using hinges at joints, should be strong enough to sustain against various loads (wind, snow, self load, etc.) and factors causing deteriorations. Shape, sizes,constructional material and methods, etc should be skillfully worked out as per requirement and opportunity exists considering climate, topography, soil, space availability, and foremost is cost and marketing positions. Construction should also provide opportunity for cost effective climate control system.